Person‐Oriented Research Ethics to Address the Needs of Participants on the Autism Spectrum. Issue 5 (16th September 2020) - Cascio, M. Ariel; Weiss, Jonathan A.; Racine, Eric
ABSTRACT: Research ethics scholarship often attends to vulnerability. People with autism may be vulnerable in research, but are also vulnerable to unjust exclusion from participation. Addressing the needs of participants with autism can facilitate inclusion and honor the bioethics principle of respect for persons while accounting for risk and vulnerability. Drawing from a review of the literature and informed by a moral deliberation process involving a task force of stakeholders (including autistic people and parents of autistic people), we use the model of person‐oriented research ethics to identify several practical strategies researchers can use to address these needs and foster inclusion. Strategies include using multiple means of communication, addressing the sensory environment, preparing participants in advance, and accounting for social context. These practical strategies are not just methodological or design choices; they are inherently related to ethical issues. Method and design choices fulfill ethical aspirations by facilitating inclusion, reducing discomfort, and focusing on individuals.